Ball toss kinematics of different service types in professional tennis players - Carboch, J.; Tufano, J. J.; Süss, V. (International Journal of Performance Analysis in Sport, 2018)
If ball toss kinematics differ during different tennis service types, receivers may be able to identify service types or locations, possibly increasing their chances of reaching and returning incoming serves. The aim of this study was to assess the two-dimensional kinematics of the ball toss during different serve types. Professional male tennis players (n = 15) with ATP rankings of 648 ± 433 (highest 180; lowest 1431) served first (flat, slice, kick) and second serves to different locations (wide and T) from the deuce and advantage court. Using a high-speed camera (400 Hz) from the receiver`s point of view, the points of ball release (BR), vertical toss peak (TP), and racket-ball contact (RC) were analysed. The TP and RC of the kick serve occurred further to the right (18-21 and 30-35 cm, respectively) compared to other serve types from both serving sides. Compared to second serves wide, second serve to the T had a TP and RC 11 and 18 cm further to the right, respectively, but only from the deuce court. As the ball toss kinematics are unique for these serves, future research should identify whether players can use this information to successfully anticipate service type and location.